Numerical solutions of locally magnetized blood flow in the vessel filled with the porous medium - Siddiqa, Sadia; Naqvi, S.B.; Hossain, M.A. (International journal of mechanical sciences, 2019)
•In this paper two-dimensional biofluid is simulated in the rectangular channel, which is fully filled with the homogeneous porous media.•The blood flow is governed by the principles of magnetohydrodynamics and ferrohydrodynamics.•The main purpose of this study is to understand the impact of porous medium on the region where biofluid is subject to the application of localized magnetic field.•It is observed that the blood velocity can be control by adjusting the isotropic permeability which is the desirable requirement of surgical treatments for hyperthermia and cancer. In this paper two-dimensional biofluid is simulated in the rectangular vessel, which is fully filled with the homogeneous porous media. Unlike the typical Navier–Stokes equations, the blood flow is governed by the principles of magnetohydrodynamics and ferrohydrodynamics. The main purpose of this study is to understand the impact of porous medium on the region where biofluid is subject to the application of localized magnetic field. The numerical results are estimated by keeping in view the applications in the field of magneto-haemorheology. Therefore, values of all the physical parameters, used for the interpretation of results, are in accordance with the pathological state. The solutions are presented in the form of vorticity function, streamlines, temperature function contours and velocity components. It is observed that the blood velocity can be controled by adjusting the isotropic permeability which is the desirable requirement of surgical treatments for hyperthermia and cancer.